Kulturowe problemy zarządzania przedsiębiorstwem w procesach międzynarodowych przejęć i fuzji - Zając, Czesław (Cultural problems of management in the processes of an international mergers and acquisitions, 2005)
Proper recognition and effective solving of cultural problems in international mergers and acquisitions (M&A) play the important role in supporting of human resource management in the difficult period of the ownership change. "Cultural shock" caused by the cultural variety and by the "administrative" introduction of the new cultural values, the assimilation of expatriates, new managerial standards introduced by the multiauthority and the necessity of overcoming the resistance against change have to be considered as the most important cultural problems of M&A. The effective solving of these problems mentioned above is the key condition of an overcoming the psychological and social barriers of M&A.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 682-691